Dexpanthenol inhibits inflammation and apoptosis in lps-induced acute lung injury by reducing ıncreased vcam-1 and caspase-3 expressions in rats - Karakuyu, Nasıf Fatih; Özmen, Özlem (Afyon Kocatepe Üniversitesi)
This study aims to investigate the effects of Dexpanthenol (Dex), a stable alcoholic analogue of D-pantothenic acid which has anti-oxidant, antiapoptotic, and antiinflammatory properties, on lipopolysaccharide (LPS)-induced lung damage via caspase-3 (cas-3) and vascular cell adhesion molecule-1 (VCAM-1) levels. According to the experimental plan of study, thirty-two Wistar Albino rats were distributed randomly into four groups as control, LPS (5 mg/kg, intraperitoneally (i.p), single dose), LPS (30 minutes before last Dex treatment) + Dex (500 mg/kg, i.p, for 3 days) and Dex. After six hours of LPS application, lung tissues of the rats were taken for histopathological, immunohistochemical and biochemical examinations. According to results of the study, LPS caused hyperemia, neutrophil leukocyte chemotaxis and thickened septal tissue on lung. Inducing inflammation by increasing VCAM-1 expression and triggered apoptosis by increasing cas-3 expression in lung tissue. In addition, LPS decreased total antioxidant status levels, which is a marker of anti-oxidant capacity, and increased oxidative stress index and total oxidant status values, which are indicators of oxidative stress. Dex has shown its effect by reversing all these alterations and normalizing the values. These results suggest that Dex can be used as a preservative to reduce LPS-induced acute toxicity in the lung.

Bu çalışma, D-pantotenik asidin antioksidan, antiapoptotik ve antiinflamatuar özelliklere sahip stabil bir alkolik analoğu olan Dekspantenol'ün (Dex), lipopolisakkarit (LPS) kaynaklı akciğer hasarı üzerindeki etkilerini vasküler hücre adezyon molekülü-1 (VCAM-1) ve kaspaz-3 (cas-3) seviyeleri üzerinden incelemeyi amaçlamaktadır. Çalışmanın deneysel planına göre otuz iki adet Wistar Albino sıçan rastgele dört farklı gruba ayrıldı: Kontrol, LPS (5 mg/kg, intraperitoneal (ip), tek doz), LPS (son Dex uygulamasından 30 dakika önce) + Dex (500 mg/kg, ip, 3 gün boyunca) ve Dex. LPS uygulamasından 6 saat sonra sıçanların akciğer dokuları histopatolojik, immünohistokimyasal ve biyokimyasal incelemeler için alındı. Çalışmanın sonuçlarına göre LPS, akciğerde hiperemi, nötrofil lökosit kemotaksisi ve kalınlaşmış septal dokuya neden oldu. Akciğer dokusunda VCAM-1 düzeylerini artırarak inflamasyonu indükledi ve cas-3 düzeylerini artırarak apoptozu tetikledi. Ayrıca LPS, antioksidan kapasitenin bir belirteci olan total antioksidan status düzeylerini düşürürken, oksidatif stresin göstergeleri olan total oksidant status ve oksidatif stres indeks değerlerini artırdı. Dex, tüm bu değişiklikleri tersine çevirerek ve değerleri normalleştirerek etkisini gösterdi. Bu sonuçlar, Dex'in LPS kaynaklı akut akciğer hasarında toksisiteyi azaltmak için bir koruyucu olarak kullanılabileceğini düşündürdü.
Dekspantenol, sıçanlarda lps'nin neden olduğu akut akciğer hasarında artan vcam-1 ve kaspaz-3 ekspresyonlarını azaltarak inflamasyonu ve apoptozu inhibe eder
Keywords: Cas-3; Dexpanthenol; Inflammation; Lung; VCAM-1